Electrophysiological relationship between the nose and the hyoid bone complex - Susumu Mukai (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2020)
Objectives: The hyoid bone of the humans hangs in the upper part of the neck. It is connected to the styloid process via the stylohyoid ligament. The bottom edge of the hyoid bone the larynx is attached to the thyrohyoid ligament. In turn, the larynx is connected with the trachea, bronchi and lungs. These structures constitute a complex that is called the Hyoid Bone Complex (HBC). Regulating the respiration HBC operates various human actions such as drinking, laughing, singing, swallowing, vomiting-crying and breathing Upper movements of the HBC inhibit respiration whereas lower movements accelerate respiration.  Method: In this study, electrophysiological recordings were measured by using surface electrodes at the ala nasi and at the HBC during breath holding, phonation, breathing, swallowing and sniffing.  Results: Results showed that there was an electrophysiological relationship between the nose and the HBC during the examined functions.  Conclusion: Congruent movements and electrophysiological activity were observed in the two organs, suggesting that the both organs play an important role in essential human functions.